Current aspects ση the anthelmintic management of gastrointestinal tapeworms and nematodes in the dog and cat - TAPES (Δ. Κ. ΤΑΠΕΣ), D. K.; MYLONAKIS (Μ. Ε. ΜΥΛΩΝΑΚΗΣ), M. E.; PAPADOPOULOS (Η. ΠΑΠΑΔΟΠΟΥΛΟΣ), E.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Gastrointestinal parasitic infections in dogs and cats are a common problem in the clinical setting. Ascarids, hookworms, whipworms and tapeworms should be eliminated on a regular basis, not only to avoid possible health implications on the host itself, but also for the zoonotic potential of certain helminthes (ascarids, hookworms, Echinococcus spp.). Of the highly efficacious and safe medications that eliminate gastrointestinal helminths, commercially available in Greece are benzimidazoles, macrocyclic lactones, tetrahydropyrimidines and isokinolones. Since puppies, kittens, pregnant and nursing animals have a greater risk to acquire gastrointestinal parasites, more intensive anthelmintic schedules are usually instituted. In the less than 6-month old domestic carnivores, deworming should begin at the age of 2-3 weeks and proceed at biweekly intervals through the 12th week, followed thereafter by monthly administrations of the anthelmintics up to the age of 6 months. Nursing bitches and queens should be treated along with their offspring, since they often develop patent infections at that period of time. In animals older than 6 months, faecal examinations should be performed two to four times yearly, followed by the appropriate parasiticidal medication. In dogs which regularly receive heartworm preventatives, deworming schedules have to be modified according to their anthelmintic spectrum.